Autophagy and the potential linkage with the human oral diseases - Deniz Yaman; Hasibe Verdi; F Belgin Ataç (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Autophagy is a cell survival mechanism that has a key role in both physiologic and pathologic conditions. In this cellular 'clearance' process, damaged organelles and macromolecules are transported to the lysosomes for degradation. With autophagy, a protection mechanism occurs in the cell under difficult conditions including oxidative stress and lack of growth factor. Paradoxically, in autophagy under some conditions, non-apoptotic cell death can be observed via a caspase-independent pathway. Recent, studies indicated that there is a strong correlation between the composition of the oral microbiota and the pathogenesis of oral diseases, and autophagy plays a crucial role in the development of this process. This review is focused on the molecular mechanism of autophagy and its relationship with human oral diseases. In this review, the importance of the autophagy mechanism in the maintenance of oral tissue health is emphasized. After examining the studies, we observed the importance of autophagy in response to a variety of oral diseases and aimed to present this awareness. Thus, a better understanding of autophagy will be the basis for developing new therapeutic strategies in the treatment of oral diseases.